Serum concentration of thyroid hormones in abnormal and euthyroid ranges and breast cancer risk: A cohort study. Issue 12 (3rd April 2019) - Kim, Eun Young; Chang, Yoosoo; Lee, Kwan Ho; Yun, Ji‐Sup; Park, Yong Lai; Park, Chan Heun; Ahn, Jiin; Shin, Hocheol; Ryu, Seungho
Abstract : The impact of variations in serum thyroid hormone concentration within the euthyroid range on breast cancer risk remains unclear. We investigated the effect of serum thyrotropin (TSH) and thyroid hormone concentration on breast cancer risk. This cohort study involved 62, 546 Korean women, aged ≥40 years, who were free of breast cancer at baseline and underwent health examination with determination of free thyroxine (FT4) and TSH. A parametric proportional hazard model was used to estimate the adjusted hazard ratio (aHR) and 95% confidence interval (CI). During a median follow‐up of 4.8 years (interquartile range: 2.8–7.3 years), 834 incident breast cancers were identified. Compared to normal FT4 level, abnormally high serum FT4 level was associated with an increased risk of incident breast cancer with a corresponding multivariable aHR (95% CI) of 1.98 (1.02–3.83). This association tended to be stronger in postmenopausal women than in premenopausal women. Within the euthyroid range, the highest TSH tertile was associated with a lower risk of breast cancer than the lowest TSH tertile with a corresponding aHR (95% CI) of 0.68 (0.55–0.84). In contrast, highest FT4 tertile was associated with a higher risk of breast cancer than the lowest FT4 tertile. Abnormally high FT4 as well as higher FT4 within the euthyroid range were positively associated with breast cancer risk, while higher TSH concentration within the euthyroid range was negatively associated with breast cancer risk. Our findings indicate that thyroid function within both the abnormal and euthyroid ranges may contribute to the development of breast cancer. Abstract : What's new? Previous epidemiological studies have examined whether hyperthyroidism and hypothyroidism affect breast cancer risk, but associations remain unclear. This large cohort study is the first study to demonstrate the association of serum thyroid hormone concentrations in both the abnormal and euthyroid range with breast cancer development. Abnormally high FT4 as well as higher FT4 within the euthyroid range were positively associated with breast cancer risk, while higher TSH concentration within the euthyroid range was negatively associated with breast cancer risk. The findings indicate that thyroid function within both the abnormal and euthyroid ranges may contribute to the development of breast cancer.